LiNbO3 waveguides for integrated SPDC spectroscopy - Solntsev, Alexander S.; Kumar, Pawan; Pertsch, Thomas; Sukhorukov, Andrey A.; Setzpfandt, Frank (APL Photonics, 2018)
Spontaneous parametric down-conversion (SPDC) spectroscopy using photon pairs is a promising avenue towards affordable mid-infrared (MIR) spectroscopy. Here, we experimentally investigate the feasibility of using periodically poled waveguides in lithium niobate for SPDC spectroscopy applications. We find the waveguides suitable to generate wavelength non-degenerate photon pairs with one photon in the MIR spectral range with high fluence. We use this to determine the cutoff wavelengths of the waveguide mode in the MIR by performing only measurements in the near-infrared spectral range.
CRIS-Team Scopus Importer:2023-04-20